IDENTIFIKASI PROBLEMATIKA WANITA BEKERJA DI PT. INTERYASA MELUR PEKANBARU - Hamdani, Muhammad; Maemunati, Titi; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research purpose this to determine the identification of the problems of women working in PT. InteryasaMelurPekanbaru. This research uses descriptive research with a qualitative approach. Qualitative methods attempt to understand and interpret the meaning of an event interaction of human behavior in specific situations according to the researcher's own perspective. To obtain an objective conclusion, qualitative research to try to explore and break through to interpreting symptoms or problems with collecting a combination of the various issues presented in the situation. Data collection techniques in this research is by observation, interview and documentation. Data obtained from informants. Informants in this study were taken as many as four people with one person as an observer. Where the research was conducted at PT. InteryasaMelurPekanbaru. When the study was planned since this research proposal seminar and followed by the writing of undergraduate education up to the test of S1. Based on the analysis of data that has the writer suggested, outlined the following conclusions on research findings about the identification of the problems of women working in PT. InteryasaMelurPekanbaru, is as follows: 1) Problems of women working in PT. InteryasaMelurPekanbaru based on internal factor for yourself, the cost requirements for children, career, household and family income. 2) Problems of women working in PT. InteryasaMelurPekanbaru based on external factors as it has got the support of her husband, the presence of children and the support of close family (father / mother / uncle and others).3) Problems of women working in PT. Interyasa Melur Pekanbaru based relational factors are not ashousekeeper, bustleand family problems.Keywords: Identification, Problems, Working Women